Microstructure evolution and corrosion properties of Mg-Dy-Zn alloy during cooling after solution treatment - 毕广利 姜静 张帆 房大庆 李元东 马颖 郝远 (Journal of rare earths, 2016)
Microstructure evolution and corrosion properties of Mg-2Dy-0.5Zn （at.%） alloy during cooling after solution treatment were investigated. The microstructure of alloy in the solid solution state （530 oC, 12 h） was composed ofα-Mg and small amounts of （Mg, Zn）xDy phases. During cooling at a cooling rate of 2 oC/min, the 14H-type LPSO phase gradually precipitated in the grain inte-rior and its volume fraction increased with increasing cooling time. The alloy cooled for 20 min exhibited the highest hardness value. In addition, electrochemical and immersion test results indicated that the alloy cooled for 5 min exhibited small corrosion current and low corrosion rate. The good corrosion resistance of alloy was mainly attributed to the continuous distribution of LPSO phase along the grain boundary.